IMPLEMENTASI MANAJEMEN RISIKO LINGKUNGAN UNTUK MENGURANGI POTENSI PENCEMARAN AIR DI AREA PERTAMBANGAN NIKEL ( STUDI KASUS PT HENGJAYA MINERALINDO) - Amrullah; Muhammad Sundoyo; Bernard Hasibuan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Nickel mining plays an important role in supporting national economic growth; however, mining activities have the potential to generate environmental impacts, particularly water pollution caused by surface runoff, sedimentation, erosion, fuel spills, and operational waste. This study aims to analyze the implementation of environmental risk management to reduce water pollution potential in nickel mining activities at PT Hengjaya Mineralindo. The research employed a descriptive quantitative approach using the Hazard Identification, Risk Assessment and Determining Control (HIRADC) method integrated with ISO 31000:2018 and the Hierarchy of Control. Data were collected through field observations, interviews, document reviews, and risk assessments of the company's primary activities, including mining, hauling, and ore sales. The study area covers approximately 5,400 hectares of Mining Business Permit (IUP) area, supported by 375 dump trucks, 185 excavators, and 25 settling ponds. The results indicated that disposal areas, ore hauling, stockpiles, fuel stations, and workshops were the primary sources of water pollution risk. Risk assessment identified two Extreme-risk activities, eight High-risk activities, and two Medium-risk activities. After implementing controls based on the Hierarchy of Control, Extreme-risk activities decreased to zero, High-risk activities decreased to three, Medium-risk activities increased to seven, and Low-risk activities increased to two, indicating improved risk control effectiveness. Engineering controls through settling ponds, sediment traps, oil traps, drainage systems, environmental inspections, and routine water quality monitoring significantly reduced water pollution potential while supporting the implementation of Good Mining Practice. The study concludes that integrating ISO 31000:2018, the HIRADC method, and the Hierarchy of Control provides an effective framework for improving environmental risk management and supporting sustainable nickel mining operations.